Pengaruh Audit Tenure, Rotasi Audit, Dan Fee Audit Terhadap Kualitas Audit Pada Perusahaan Idx80 Yang Terdaftar Di Bursa Efek Indonesia Tahun 2021-2023 - Tiarafytha Tahun; I Komang Arthana; Maria Prudensiana Leda Muga (Indo-Fintech Intellectuals: Journal of Economics and Business, 2024)
The incident of poor audit quality explains that the auditor is fully responsible for the entire audit process until the final audit results are obtained. This study aims to partially examine the effect of audit tenure, audit rotation and audit fees on audit quality. The data used is secondary data obtained from consolidated annual reports and audited financial reports in IDX80 companies for 2021-2023. The population in this study were IDX80 companies listed on the Indonesia Stock Exchange in 2021-2023 with purposive sampling technique for sampling so that 47 sample companies were obtained with 141 observed financial reports. The analysis technique used is binary logistic regression analysis with associative survey quantitative methods. The results obtained show that audit tenure and audit rotation partially have a positive but not significant effect on audit quality, while audit fees have a significant positive effect on audit quality. The contribution of this research is that audit quality measured using the organization and governance of Public Accounting Firms in accordance with the Decree of the Executive Board of the Indonesian Institute of Certified Public Accountants No. 4 of 2018 concerning Guidelines for Audit Quality Indicators at Public Accounting Firms.